2018
DOI: 10.1016/j.pvr.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Intra-host sequence variability in human papillomavirus

Abstract: Human papillomaviruses (HPVs) co-evolve slowly with the human host and each HPV genotype displays epithelial tropisms. We assessed the evolution of intra HPV genotype variants within samples, and their association to anogenital site, cervical cytology and HIV status. Variability in the L1 gene of 35 HPV genotypes was characterized phylogenetically using maximum likelihood, and portrayed by phenotype. Up to a thousand unique variants were identified within individual samples. In-depth analyses of the most preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 63 publications
2
37
0
Order By: Relevance
“…Potentially even larger intrahost variation has been reported if HIV-positive women are included (22). Limitations of our study thus include restriction by design to the intraindividual longitudinal perspective, restriction to women developing squamous cervical lesions, the limited inference to other ethnic groups than Caucasians, and the small number of controls that precluded more sophisticated analyses by, for example, casecontrol status over time.…”
Section: Discussionmentioning
confidence: 98%
“…Potentially even larger intrahost variation has been reported if HIV-positive women are included (22). Limitations of our study thus include restriction by design to the intraindividual longitudinal perspective, restriction to women developing squamous cervical lesions, the limited inference to other ethnic groups than Caucasians, and the small number of controls that precluded more sophisticated analyses by, for example, casecontrol status over time.…”
Section: Discussionmentioning
confidence: 98%
“…Traditionally, PVs have been thought to evolve slowly because they replicate by co-opting high-fidelity host cellular DNA polymerases that have an error rate of about 4.3 × 10 − 5 substitutions per nucleotide site per year (Korona et al 2011). The general assumption is that PVs have coevolved with their hosts (Chen et al 2009a;Bravo and Felez-Sanchez 2015;Dube Mandishora et al 2018). Selection pressures due to host immune responses differ among PV genes and result in these genes displaying different substitution rates.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The prevalence of HPV infection in women worldwide is estimated to range from 2-44% [1]. It has been demonstrated that the majority of reproductive-age women who are sexually active have been exposed to one or more types of HPV in the genitals (approximately 50%) and oral cavity (30%) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Infection with hrHPV could be aggravated by immunosuppression, such as that observed in HIV patients [2]. Developing countries present the highest prevalence of HPV [5] and HIV [6] infections.…”
Section: Introductionmentioning
confidence: 99%